EFFECT ANALYSIS OF INFLATION, EXPORTS AND IMPORTS ON ECONOMIC GROWTH IN INDONESIA - Firdaus, Ellina Nuril; Septiani, Yustirania (Transpublika Publisher, 2022)
A country's economic development is significantly influenced by economic growth. A nation can use economic growth indicators to inform its economic policy decisions and help it achieve its economic objectives. This study aims to examine the effect of inflation, exports and imports, on Indonesia's economic growth between 1990 and 2020. There are a number of issues in this study, and the error correction model, or ECM, is the model used in the data used to determine how to resolve these issues (Error Correction Model). The ECM (Error Correction Model) method calculations' findings are used to explain why there is a long-term negative relationship between inflation and economic growth. Additionally, exports have a short-term negative impact on Indonesia's economic growth. In order for economic activities to run smoothly and economic growth to increase, it is hoped that export-import activities in Indonesia can stabilize economic growth and inflation from year to year.